Electrooptical properties of liquid crystal n-pentil-n´-cyanobifenil with J-aggregates of astrofloxine - Piryatinski, Yu.P.; Furier, M.S.; Nazarenko, V.G. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2001)
It is shown that organic nanocrystallites - J-aggregates - can be formed and oriented in a liquid crystalline matrix. External electric field can reorient and destroy these nanocrystallites. Transmission and photoluminescence spectra of astrofloxine solutions in the nematic liquid crystal are investigated in d.c. and a.c. electric fields with the frequencies of 1 Hz-1 kHz and amplitudes F = 1.2×104 V•cm⁻¹. Intense photoluminescence was observed at two-photon excitation. Efficiency of IR laser radiation transformation into visible photoluminescence was as high as 10%.